PENGARUH PEMBELAJARAN KURIKULUM 2013 TERHADAP MOTIVASI BELAJAR PAK SISWA KELAS VII SMP NEGERI 1 SIPOHOLON KECAMATAN SIPOHOLON KABUPATEN TAPANULI UTARA TAHUN PEMBELAJARAN 2017/2018 - Sianipar, Nopela (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, The purpose of this study is to determine the effect of applying the 2013 curriculum learning to the motivation of learning PAK of the students of classes VII SMP Negeri 1 Sipoholon Academic Year 2017/2018. The method used in this research is the method of inferential statistics. The population is all student classes VII in SMP Negeri 1 Sipoholon 2017 year with the number of 160 students and sample 80 students by using random sampling technique . The instrument of this research is a closed questionnaire of 53 items. The results of data analysis showed that there is a positive impact of the application of the 2013 curriculum learning on the motivation of learning PAK in class VII SMP Negeri 1 Sipoholon Academic Year 2017/2018 of 9.3% with hypothesis test using F test obtained Fobt Ftab is 7,989 1,39 thus H0 rejected and Ha accepted. Keywords: Learning, Curriculum 2013, Motivation of Learning Christian Subjek